PERBANDINGAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DAN GROUP INVESTIGATION PADA MATERI SISTEM PENCERNAAN MANUSIA DI KELAS VIII SMP TAMAN SISWA PEMATANGSIANTAR TAHUN PELAJARAN 2020/2021 - DAMANIK, RISJUNARDI (Jurnal Metabio, 2021)
This study was conducted with the aim of determining the differences in student learning outcomes using the Word Square and Group Investigation learning models on the human digestive system material in class VIII of Taman Siswa Junior High School, Pematangsiantar, in the 2020/2021 Academic Year. The population in the study were all class VIII students of Taman Siswa Junior High School, Pematangsiantar, in the 2020/2021 Academic Year, consisting of 6 classes totaling 215 students and a sample of 64 people, namely class VIII-3 as the experimental class I and VIII 2 as the experimental class II. From the results of the hypothesis testing, it was obtained that t count (6.55) > t table (1.99), at a significance level of α = 0.05 and degrees of freedom = 62, then Ho was rejected and Ha was accepted, meaning there were differences in student learning outcomes using the Word Square and Group Investigation learning models on the human digestive system material in class VIII of Taman Siswa Junior High School, Pematangsiantar, in the 2020/2021 Academic Year. It was concluded that there was a difference in student learning outcomes using the Word Square learning model on the human digestive system in eighth grade students of Taman Siswa Middle School, Pematangsiantar, in the 2020/2021 academic year, compared to those using the Group Investigation learning model.